2020
DOI: 10.1007/s11005-020-01288-8
|View full text |Cite
|
Sign up to set email alerts
|

Log expansions from combinatorial Dyson–Schwinger equations

Abstract: We give a precise connection between combinatorial Dyson-Schwinger equations and log-expansions for Green's functions in quantum field theory. The latter are triangular power series in the coupling constant α and a logarithmic energy scale L -a reordering of terms as G(α, L) = 1± j≥0 α j H j (αL) is the corresponding log-expansion. In a first part of this paper, we derive the leading-log order H 0 and the next-to (j) -leading log orders H j from the Callan-Symanzik equation. In particular, H j only depends on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The seminal work of Kreimer and Connes showed that there is an underlying Hopf-algebraic structure to the renormalization of quantum field theory (QFT) [28,29,61]. This new perspective has led to deep insights into QFT, and also to novel computational methods that have enabled significant progress in higher order perturbative computations [14,16,17,20,22,23,27,60,62,63,64,81,83,84,85,88,89,90,91]. The Hopf-algebraic formulation of QFT is inherently perturbative in nature, so an important open question is to understand how the non-perturbative features of QFT arise naturally within the perturbative Hopf algebra structure.…”
Section: Introductionmentioning
confidence: 99%
“…The seminal work of Kreimer and Connes showed that there is an underlying Hopf-algebraic structure to the renormalization of quantum field theory (QFT) [28,29,61]. This new perspective has led to deep insights into QFT, and also to novel computational methods that have enabled significant progress in higher order perturbative computations [14,16,17,20,22,23,27,60,62,63,64,81,83,84,85,88,89,90,91]. The Hopf-algebraic formulation of QFT is inherently perturbative in nature, so an important open question is to understand how the non-perturbative features of QFT arise naturally within the perturbative Hopf algebra structure.…”
Section: Introductionmentioning
confidence: 99%
“…(n + 1) (which is asymptotically equivalent to n k ). Therefore the asymptotic estimate of Theorem 5.2 leads (after simplification) to One naturally recover estimate (10).…”
Section: Typementioning
confidence: 93%
“…A chord (a, b) in a diagram is terminal if every chord (c, d) intersecting (a, b) satisfies c < a. Equivalently, a chord (a, b) is terminal if there is no chord (a , b ) satisfying a < a < b < b .It means that terminals chords correspond to the vertices with no outgoing edge in the intersection graph of their diagram. For example, chords (4, 6) and(7,10) are terminal in the right diagram ofFigure 1, and chords 4, 6, 7 are terminal in the diagram ofFigure 3.…”
mentioning
confidence: 99%
“…The seminal work of Kreimer and Connes showed that there is an underlying Hopf algebraic structure to the renormalization of quantum field theory (QFT) [1][2][3]. This new perspective has led to deep insights into QFT, and also to novel computational methods that have enabled significant progress in higher order perturbative computations [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The Hopf algebraic formulation of QFT is inherently perturbative in nature, so an important open question is to understand how the nonperturbative features of QFT arise naturally within the perturbative Hopf algebra structure. In a recent paper [22] we showed how this works for 4 dimensional massless Yukawa theory, using Écalle's theory of resurgent trans-series and alien calculus [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%